What is a child? - Tucker, Nicholas; Bennett, Anna (London : Open books, 1977)
"A child has small hands, small feet and small ears, but that does not mean they have small ideas"--
Translated from the Italian.
Keywords: Child development; In; Child development; Children; Individuality